Cross-border e-commerce and enterprise green innovation - Zhang, Shengyang; He, Li; Zhang, Yu (Frontiers in Sustainability, 2025)
The rapid development of cross-border e-commerce has not only helped businesses expand into international markets but also facilitated technological exchanges and resource sharing among enterprises, ultimately promoting green innovation. This study is based on data from Chinese listed companies from 2013 to 2023, utilizing web scraping technology to extract corporate announcements and employing a cross-border e-commerce keyword dictionary to identify specific time points when companies engaged in cross-border e-commerce activities. These time points are treated as policy shock events, and a difference-in-differences model is employed for empirical analysis. The findings reveal that engaging in cross-border e-commerce significantly enhances a company’s level of green innovation. Mechanism analysis indicates that cross-border e-commerce indirectly promotes increases in green patent applications by alleviating firms’ financial constraint and promoting their digital transformation, while environmental information disclosure also plays a positive moderating role. Heterogeneity analysis shows that this promotional effect is more pronounced among high-tech enterprises, firms in high-pollution industries, large state-owned enterprises, and companies in China’s central and western regions. The study’s conclusions provide a reference for enterprises to achieve sustainable development through cross-border e-commerce activities.